Implementación de contabilidad de costos por órdenes de producción de envases de vidrio de la empresa Crevigo S.A. En la ciudad de Loja período julio a septiembre 2013 - León Seraquive, Karina Vanessa (2014)
This research report is a collection of accounting information and financial performance of the company "CREVIGO S.A. ", whose theme is "Implementing cost accounting by orders of production of glass packaging in the company Crevigo S. A. in the city of Loja period July to September 2013", the main objective is the control, representation and credible and reliable assessment of the production process of this company, making the practice of the accounting system for the costs of production of glass containers, based on generally accepted accounting principles and standards and other applicable laws. The development of the deployment costs by orders of production of glass bottles in the company Crevigo S.A. , allowed to determine the exact cost of production of glass packaging, determine the orderly and systematic process for the production system and control of accounting documents of the same in order to ensure that the information gathered was as accurate as possible, with the development of production orders, orders to provide material, kardex cards, cards clock, time card and a worksheet, it meets the proposed target for the development of the present thesis work to implement the cost accounting by orders of production of glass packaging in the company Crevigo S. A. in the city of Loja period July to September 2013, and concludes with the delivery of the respective financial statements: State of Integral Results, Statement of Financial Position, cash flow and State of changes in equity; as well as the formats of all the ancillary documents. The implementation of cost accounting for production orders of glass bottles in the company Crevigo S. A. in the city of Loja period July to September 2013, delivered to the manager of the company reliable data for effective decision-making and negotiation, improve the control of production resources of the company, for this reason I recommend using the accounting process raised in the present thesis for their accounting and get real costs of their products.